Migration, land loss and costs to 2100 due to coastal flooding under the IPCC AR6 sea-level rise scenarios and plausible adaptation choices - Caridad Ballesteros; Daniel Lincke; Robert J. Nicholls; Jack Heslop; Jochen Hinkel; Víctor Malagón-Santos; Aimée B. A. Slangen; Aimée B. A. Slangen (Frontiers in Marine Science)
Sea-level rise (SLR) through the twenty-first century and beyond is inevitable, threatening coastal areas and their inhabitants unless there is appropriate adaptation. We investigate coastal flooding to 2100 under the full range of IPCC AR6 (2021) SLR scenarios, assuming plausible adaptation. The adaptation selects the most economically robust adaptation option: protection or retreat. People living in unprotected coastal areas that are frequently inundated (below 1-in-1-year flood level) are assumed to migrate, and the land is considered lost. Globally, across the range of SLR and related socioeconomic scenarios, we estimate between 4 million and 72 million people could migrate over the twenty-first century, with a net land loss ranging from 2,800 to 490,000 km2. India and Vietnam consistently show the highest absolute migration, while Small Island Developing States are the most affected when considering relative migration and land loss. Protection is the most robust adaptation option under all scenarios for 2.8% of the global coastline, but this safeguards 78% of the global population and 91% of assets in coastal areas. Climate stabilisation (SSP1–1.9 and SSP1–2.6) does not avoid all coastal impacts and costs as sea levels still rise albeit more slowly. The impacts and costs are also sensitive to the socioeconomic scenario: SSP3–7.0 experiences higher migration than SSP5–8.5 despite lower SLR, reflecting a larger population and lower GDP. Our findings can inform national and intergovernmental agencies and organisations on the magnitude of SLR impacts and costs and guide assessments of adaptation policies and strategies.